Persepsi Guru PPKn dan Peserta Didik Terhadap Kekerasan di SMP Al-Quran Putra Bahari Kota Ternate - Amaludin Hamiru; Irwan Djumat; Hasmawati Hasmawati (Universitas Khairun, 2022)
Background The problems in this study are: the causes of violence, perceptions of civics teachers and students towards violence at SMP Al-Quran Putra Bahari Ternate City. This study aims to find out opinions and attitudes in overcoming violence and forms of violence as well as efforts to overcome violence at SMP Al-Quran Putra Bahari Ternate City. The research used in this study is qualitative research on case studies, namely: in- depth research on programs, events, processes, activities of one or more people. The purpose of this case study research is to seek to find meaning, examine the process and obtain a deep and complete understanding and understanding of a particular individual, group, or situation. For the data collected the authors used interview, observation, and documentation techniques. The data collected can be analyzed in depth. Based on the results of the research that the author conducted, and analyzed at SMP AL-Quran Putra Bahari Kota Ternate, it can be concluded that: From the results of the research that the author conducted at SMP Al-Quran Putra Bhari, Ternate City. It can be concluded that violence in the world of education is not good because it can damage the physical and psychic of students but rather an emphasis because it is a way or last resort in educating but not to the point of physically or psychologically injuring children. Keywords: Perception, violence, learners.